2006
DOI: 10.1152/ajpendo.00429.2005
|View full text |Cite
|
Sign up to set email alerts
|

LKB1-AMPK signaling in muscle from obese insulin-resistant Zucker rats and effects of training

Abstract: is a key regulator of fat and carbohydrate metabolism. It has been postulated that defects in AMPK signaling could be responsible for some of the metabolic abnormalities of type 2 diabetes. In this study, we examined whether insulin-resistant obese Zucker rats have abnormalities in the AMPK pathway. We compared AMPK and ACC phosphorylation and the protein content of the upstream AMPK kinase LKB1 and the AMPKregulated transcriptional coactivator PPAR␥ coactivator-1 (PGC-1) in gastrocnemius of sedentary obese Zu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
68
3
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 66 publications
(74 reference statements)
11
68
3
2
Order By: Relevance
“…the motor unit size recruitment principle). These exercise studies (45)(46)(47)(51)(52)(53), and our present transfection studies, in which PGC-1␣ is up-regulated in only some muscle fibers, do not invalidate the observations that metabolic changes are induced on a per g or per whole muscle basis. In exercise studies (53), as well as in the present studies, there will be a considerable heterogeneity of responses in PGC-1␣, and in other parameters, among muscle fibers, ranging from no change to very large changes in some muscle fibers.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…the motor unit size recruitment principle). These exercise studies (45)(46)(47)(51)(52)(53), and our present transfection studies, in which PGC-1␣ is up-regulated in only some muscle fibers, do not invalidate the observations that metabolic changes are induced on a per g or per whole muscle basis. In exercise studies (53), as well as in the present studies, there will be a considerable heterogeneity of responses in PGC-1␣, and in other parameters, among muscle fibers, ranging from no change to very large changes in some muscle fibers.…”
Section: Discussionsupporting
confidence: 55%
“…Others had already shown that there was not a strong relationship between insulin-signaling proteins and the metabolic characteristics of rodent skeletal muscle (72), that PGC-1␣ did not induce insulin-signaling proteins in L6 myotubes (3), and that exercise training, which increases PGC-1␣ (46), also failed to up-regulate insulin-signaling proteins (73). However, unlike studies in PGC-1␣-transfected L6 myotubes (3), we did observe a greater insulin-stimulated phosphorylation of Akt2 in PGC-1␣-transfected muscles.…”
Section: Pgc-1␣-induced Fatty Acid Oxidation-mentioning
confidence: 99%
“…Other studies have shown that obese insulin-resistant Zucker rats have reduced AMPK activity and related signaling abnormalities in skeletal muscle (37)(38)(39). These reports indicate that skeletal muscle AMPK activity can be altered if the obesity and/or insulin resistance is severe, and, in this situation, lower AMPK activity may contribute to the obese and insulin-resistant phenotype (39).…”
Section: Discussionmentioning
confidence: 90%
“…These reports indicate that skeletal muscle AMPK activity can be altered if the obesity and/or insulin resistance is severe, and, in this situation, lower AMPK activity may contribute to the obese and insulin-resistant phenotype (39). Importantly, exercise training can reverse abnormalities of impaired AMPK signaling in obese Zucker rats, which may contribute to the beneficial effect of exercise on improvement of insulin resistance (39). Interestingly, it has also been reported that suppression of AMPK signaling is involved in tumor necrosis factor-induced skeletal muscle insulin resistance (40).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to its role on contraction-induced muscle glucose transport and fatty acid oxidation with a single bout of exercise, it has also been hypothesized that the repetitive increases in muscle AMPK activity that occur during physical training with each exercise bout lead to increased mitochondrial biogenesis and function (13,14). Increases in mitochondrial number/function with physical training are thought to occur, in part, through a mechanism that involves AMPK-mediated peroxisome proliferator-activated receptor coactivator-1 (PGC-1) gene expression (15).…”
mentioning
confidence: 99%